Oral myiasis in a patient with HIV manifestations and neurologic toxoplasmosis treated by ivermectin - Pires, Willian Ricardo [UNESP]; de Oliveira Puttini, Igor [UNESP]; de Oliva, André Hergesel [UNESP]; Jacob, Ricardo Garcia Mureb [UNESP]; Figueira, Heldo Cesar [UNESP]; Sonoda, Júnior Celso Koogi [UNESP]; Faverani, Leonardo Perez [UNESP]; Souza, Francisley Ávila [UNESP]; Júnior, Idelmo Rangel Garcia [UNESP] (Wolters Kluwer, 2018)
Myiasis has been defined as a pathologic condition where dipterous larvae are lodged in mammalian hosts causing an infestation, which feeds on living or dead tissue for at least a certain period inside the host and develops itself as parasites. In humans, the most commonly affected sites are the nose, eyes, skin wounds, sinuses, lungs, ears, gut, gall bladder, vagina, nasal cavities, and rarely the mouth because the oral tissues are rarely exposed to the external environment. The etiology of oral myiasis is usually related to local factors such as poor oral hygiene, periodontal disease and labial incompetence, and systemic factors such as neurologic deficits.
Keywords: AIDS serodiagnosis; Cerebral; Ivermectin; Myiasis; Toxoplasmosis